Landasan Filosofis Dan Psikologis Dalam Pembelajaran Kontekstual - Safriadi Safriadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Contextual learning is a teaching strategy that emphasizes the involvement of students in full process to be able to find the material studied and relate them to real life situations that encourage students to be able to apply it in their lives. The cornerstone of the philosophy of contextual learning is constructivism, which is a learning process that conditioned the student to make the process of actively building new concepts and new knowledge based on the data. Therefore, the learning process should be designed and managed in such a way so as to encourage students to organize his own experiences into meaningful knowledge. In accordance with the underlying philosophy that knowledge is formed because of the active role of the subject, it is considered from the psychological angle, contextual learning is grounded in cognitive psychological flow. According to this flow of learning occurs because of an individual's understanding of the environment. Learning is not a mechanical event such as the relationship of stimulus and response. Learning involves a mental process that does not look like emotions, interests, motivation and ability. That which appears is essentially a manifestation of lack of encouragement that develops in a person. As a mental events, human behavior is not merely a physical movement, but more important is the driving factor is behind the physical movement. Humans have a need that is inherent in him. The need is what drives people to behave.